[PP.10.20] IMBALANCE BETWEEN T REGULATORY AND TH17 LYMPHOCYTE SUBSETS IN PATIENTS WITH RESISTANT HYPERTENSION AND PRIMARY ALDOSTERONISM. (September 2017) - Kaszuba, A.; Konior, A.; Mikolajczyk, T.; Prejbisz, A.; Januszewicz, A.; Guzik, T.
Abstract : Objective: In the past several years, it has become evident that inflammation contributes to the elevation of blood pressure. Evidence from experimental models of hypertension and hypertensive patients suggests imbalance of T effector and regulatory subsets in hypertension. In our study we aimed to quantify blood T lymphocyte subsets in subjects with secondary hypertension- resistant hypertension (RHT) and primary aldosteronism (PA) characterized by increased BP levels, augmented cardiovascular risk in comparison to control subjects matched for age, sex and BMI (CG). Design and method: In an ongoing study we included 29 patients (20 M, 9F, mean age 54.9 ± 11.5) with RHT, 26 patients with PA (14 M, 12F, mean age 54.8 ± 12.6) and 30 CG patients (15 M, 15F, mean age 50.4 ± 11.2). T cells characteristics from peripheral blood samples were studied by multicolour flow cytometry with intracellular staining for foxp3. The concentration of the angiotensin II in patients' blood samples was determined by radioimmunoassay method. Data were analyzed using T test with Bonferroni correction for multiple comparisons. Results: Patients with RHT and PA were characterized by significantly higher BP values on ambulatory blood pressure monitoring as compared with CG. In comparison to CG, patients with RHT and PA had lower percentage of CD4+25+foxp3+ T cells (Tregs): consecutively RHT 5.5 ± 3.2%; PA 5.8 ± 4.3% vs CG 9.9 ± 10.6%; p = 0.01, p = 0.084. However, the percentage of CD3+CD4+IL-17+ T cells was higher in RHT 19 ± 20% and PA 12.9 ± 16.2%, vs CG 3.7 ± 2.4%; p < 0.01, p = 0.04. In patients with PA, in comparison to CG and RHT, lower angiotensin II concentration and higher aldosterone to renin ratio was observed. Conclusions: Our results indicate, that dysregulation of T cell activation with very significant increase of proinflammatory T cells and decrease in Tregs may play a role in the pathogenesis of RHT and PA, regardless of the renin-angiotensin-aldosterone activation.